Ketepatan Penyampaian Laporan Keuangan Desa di Kabupaten Bone - Nurmiati Irvan; Fina Diana; Murbayani Murbayani; Bastian Lubis; Andi Risnah (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2021)
This research was conducted in Bone Regency with the aim of knowing the accuracy of submitting village financial reports. this type of research is quantitative research. The population in this study were all village heads or village financial management apparatus. by using a research instrument in the form of a questionnaire which is a source of primary data and secondary data in the form of village financial reports. The data analysis technique in this study uses descriptive statistics, namely statistics used to analyze the data that has been collected as it is without the intention of making generally accepted conclusions or generalizations. Furthermore, data reduction is carried out by selecting the main things, focusing on the most important things, then after the data is reduced, the next step is to show the data. After analyzing the data, the results obtained in the study are that there are still some villages that are not timely in submitting their financial reports, this is caused by several factors, including the quality of human resources which is the key to the creation of quality financial reports supported by information technology. and internal control system